Dasar-Dasar Ekonomi Dan Kebijakan Nasional: Perekonomian 3 Sektor - Miftahul Hayati; Laila Adinda Al Maida; Sabrina Septiani (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This study aims to assess the effectiveness of community service activities based on economic education and national policy at SMA PGRI 56 Ciputat. Through an active and interactive approach, students are involved in understanding basic economic concepts, resource management, production processes, economic systems, and the importance of national policies in supporting community growth and independence. The activities were carried out through lectures, discussions, and preliminary surveys to adjust to the participants' needs. The results show that participants gained new insights relevant to real-world conditions, thereby increasing their understanding, motivation to learn, and awareness of the role of the younger generation in regional economic development. However, time and resource constraints posed challenges, necessitating continuous evaluation and more structured follow-up. Overall, this activity was deemed effective in fostering economic awareness, the importance of national policy, and entrepreneurial values among Generation Z.